اسلامی عبادات اور اجتہاد بالمقاصد (مذاہبِ اربعہ کے تناظر میں): Islamic Worships and Ijtihad Bil Maqasid (In the context of four school of Islamic jurisprudence) - Dr. Amin Ali; Dr. Syed Yasir Ali (Al Manhal Research Journal, 2024)
Islam is not only a complete code of life, but also provides a complete guidance material for the newly emerging problems of today’s life. Islam has not only allowed the jurists of the Ummah to carry out reliability, speculation and ijtihad after the Book of Allah, the Sunnah of the Messenger of Allah ﷺ and the consensus of the Companions, keeping in mind the same principles and skills, but has also declared it a recommended practice from the point of view of Shari’ah necessity. With the passage of time, a series of new problems arose, for which, by understanding the mysteries of the holy law, a form of ijtihad and inference should be presented in accordance with the needs and requirements of the time, from which the people Not only should there be ease in the collective form, but at the same time, there should be no disturbance in the mysteries and secrets of the rules and regulations of Islam. This modern term is known as Ijtihad-Bil-Maqasid, the main purpose of this research will be to examine the necessity and importance of Ijtihad-Bil-Maqasid and the orders in some of the issues rose in the chapter of worship in the modern era. This research paper contains meanings of Maqasid, definitions of Ijtihad –Bil- Maqasid, its terms & conditions and some worships problems in modern era with their solutions in the light of Ijtihad –Bil- Maqasid In the context of four school of Islamic jurisprudence.